(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: This prospective randomized controlled study evaluated the effects of drinking a carbohydrate-rich solution 2 hours before surgery on gastric residual volume, blood glucose levels, serum electrolytes, and postoperative nausea and vomiting in patients undergoing open surgery under general anesthesia at Hai Phong hospital of Obstetrics and Gynecology. Subjects and Methods: 80 patients were enrolled after screening and randomly assigned to two groups of 40 patients each: a complete fasting group following the Ministry of Health guidelines and a carbohydrate group receiving a carbohydrate-rich drink 2 hours before surgery. Results: The mean gastric residual volume was 8.3 ± 7.6 ml in the fasting group and 7.5 ± 8.2 ml in the carbohydrate group, with no statistically significant difference (p > 0.05), and no cases of gastric regurgitation were observed during anesthesia induction. Mean venous blood glucose levels at 30 minutes after induction and 2 hours after recovery were comparable between groups and showed no significant differences (p > 0.05). The incidence of nausea and vomiting before surgery and at 2 hours after recovery was low in both groups, with no significant differences. Serum electrolyte concentrations (Na⁺, K⁺, Cl⁻) measured before anesthesia and 2 hours after recovery remained within normal physiological ranges in both groups and did not differ significantly (p > 0.05). Conclusion: These findings indicate that administration of a carbohydrate-rich solution 2 hours before surgery is safe and effective, without increasing gastric residual volume, causing significant hyperglycemia, electrolyte imbalance, or increasing postoperative nausea and vomiting.